2017
DOI: 10.1016/j.radi.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of oncology healthcare practitioners towards smoking cessation: A systematic review of the facilitators, barriers and recommendations for delivery of advice and support to cancer patients

Abstract: This document is the author deposited version. You are advised to consult the publisher's version if you wish to cite from it. CONLON, Katy, PATTINSON, Laura and HUTTON, Daniel (2017). Attitudes of oncology healthcare practitioners towards smoking cessation: A systematic review of the facilitators, barriers and recommendations for delivery of advice and support to cancer patients. Radiography, 23 (3), 256-263. Published version Copyright and re-use policySee http://shura.shu.ac.uk/information.html Sheffield Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…A perceived lack of skills prevented healthcare professionals from addressing physical activity in six reviews, four of which focused on studies based in primary care settings (Gentry et al 2017). Six of the twenty systematic reviews cited a perceived lack of behavior change training (Conlon et al 2017). Seven of the twenty reviews reported that healthcare professionals perceived a lack of confidence in their ability to facilitate positive behavior changes in patients (Vogt et al 2005).…”
Section: Perceptions Of the Knowledge Or Skills Needed To Support Behmentioning
confidence: 99%
“…A perceived lack of skills prevented healthcare professionals from addressing physical activity in six reviews, four of which focused on studies based in primary care settings (Gentry et al 2017). Six of the twenty systematic reviews cited a perceived lack of behavior change training (Conlon et al 2017). Seven of the twenty reviews reported that healthcare professionals perceived a lack of confidence in their ability to facilitate positive behavior changes in patients (Vogt et al 2005).…”
Section: Perceptions Of the Knowledge Or Skills Needed To Support Behmentioning
confidence: 99%
“…A recent systematic review 22 highlighted the attitudes of oncology practitioners towards smoking cessation. This review identified the key barriers to smoking cessation were; lack of training, perception that the intervention may be harmful through increased stress and guilt, lack of confidence in cessation, lack of knowledge and oncology practitioners do not associate smoking cessation to be part of their role.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The motivation of Therapeutic Radiographers to deliver brief interventions is evident 20,21 The barriers and facilitators identified in paper 1, a recent systematic review 22 were used to structure the pre focus group questionnaires which subsequently informed the development of the focus group topic guide (Appendix A). This work, paper 2, will inform part 3 and paper 3, the development of an oncology specific training resource to equip practitioners with the confidence and competence to deliver VBA.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations